2004
DOI: 10.1111/j.1744-7348.2004.tb00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term salt stress on antioxidant defence systems, leaf water relations and chloroplast ultrastructure of potato plants

Abstract: SummaryThe effect of long‐term (30 days) NaCl treatments (100 mM and 200 mM) on the activity of some antioxidant enzymes, level of antioxidant metabolites, water relations and chloroplast ultrastructure, was studied in potato (Solanum tuberosum cv. Désirée) leaves. Salt stress negatively affected relative water content, leaf stomatal conductance and transpiration rate. In treated plants, proline was enhanced, but there was a significant decrease in ascorbate and proteins. Total superoxide dismutase activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 53 publications
8
63
2
1
Order By: Relevance
“…In our study, the increase in NaCl concentration in media reduced growth rate of potato callus lines cultivated in the presence of NaCl. In fact, the reduction in growth is a common phenomenon of salt stressed plants (Benavídes et al 2000, Fidalgo et al 2004, Sotiropoulos et al 2006, which has also been observed in cultured cells on medium supplemented with NaCl (Rus et al 1999, Shankhdhar et al 2000, Gu et al 2004, Lutts et al 2004, Niknam et al 2006. As reported by Zhu (2001), slower growth is an adaptive feature for plant survival under stress and the extent of salt tolerance often appears to be inversely related to growth rate.…”
Section: Discussionmentioning
confidence: 88%
“…In our study, the increase in NaCl concentration in media reduced growth rate of potato callus lines cultivated in the presence of NaCl. In fact, the reduction in growth is a common phenomenon of salt stressed plants (Benavídes et al 2000, Fidalgo et al 2004, Sotiropoulos et al 2006, which has also been observed in cultured cells on medium supplemented with NaCl (Rus et al 1999, Shankhdhar et al 2000, Gu et al 2004, Lutts et al 2004, Niknam et al 2006. As reported by Zhu (2001), slower growth is an adaptive feature for plant survival under stress and the extent of salt tolerance often appears to be inversely related to growth rate.…”
Section: Discussionmentioning
confidence: 88%
“…Saline water irrigation negatively influenced the leaf fresh weight, without significant effects on leaf number, dry weight, and surface, supporting that salt stress mainly reduces leaf water content (Fidalgo et al 2004) [59]. Moreover, salinity stress did not exert any significant effects on SPAD values in either of genotypes, despite this stress resulting in chlorophyll damage, with a reduction in photosynthetic activity and leaf senescence acceleration (Shi and Guo, 2006;Beltrano et al 2013) [60,61].…”
Section: Field Experimentsmentioning
confidence: 85%
“…Generally, photosynthesis is inhibited by salt stress (Ma et al 1997, Sultana et al 1999, Qiu et al 2003, Koyro 2006. Salt stress also affects photosynthetic components (Ma et al 1997, Qiu et al 2003 and chloroplast ultrastructure (Fidalgo et al 2004). However, there are few reports on the effects of alkali stress on photosynthesis.…”
Section: Introductionmentioning
confidence: 99%